Exploring the intergenerational correlation of mental health in China - Qin, Xuezheng; Chen, Sharon; Hsieh, Chee-Ruey (Unpublished, 2019)
Background The rising global prevalence of mental illnesses such as depression, in combination with the stylized fact of low treatment rate for such illnesses, raises a serious public and academic concern on whether the untreated mental illness will further increase the disease prevalence over the next generation through the channel of intergenerational transmission. Objective This paper addresses the intergenerational correlation of mental health in China, by using a national representative survey dataset obtained from China Family Panel Studies. Methods We use a full 20-question version of the CES-D (Center for Epidemiologic Studies Depression) questionnaire to measure an individual’s mental health status. Based on a parent-child matched sample, we use a stepwise regression approach to estimate the impacts of parents’ CES-D scores on their children’s CES-D scores. Results We find that both father’s and mother’s mental health have significant impact on their children’s mental health. In addition, we find that parental mental health appears to have a greater impact on the mental health in the next generation than maternal mental health does, which is contrary to what most literature portrays. Conclusion Our results suggest that both maternal and paternal mental health have significant impacts on the mental health of their offspring, although paternal mental health appears to have a greater effect. Additionally, intergenerational correlation of mental health is present in all studied areas and subpopulations of China.